Construction and Demolition Waste-Derived Feedstock: Fuel Characterization of a Potential Resource for Sustainable Aviation Fuels Production - Bach, Quang-Vu; Fu, Jinxia; Turn, Scott (Frontiers in Energy Research, 2021)
Detailed characterization of physical and fuel properties of construction and demolition waste (CDW) can support research and commercial efforts to develop sustainable aviation fuels. The current study reports time-series data for bulk density, mineral composition, reactivity, and fuel properties (proximate analysis, ultimate analysis, heating value and ash fusibility) of the combustible material fraction of samples mined from an active CDW landfill on the island of Oʻahu, Hawaiʻi. The fuel properties are in ranges comparable to other reference solid wastes such as demolition wood, municipal solid wastes, and landfilled materials. Ash fusion temperatures (from initial deformation to fluid deformation) among the samples were found to lie in a narrow range from 1,117 to 1,247°C. Despite higher ash contents, the CDW derived feedstock samples had comparable heating values to reference biomass and construction wood samples, indicating the presence of higher energy content materials (e.g., plastics, roofing material, etc.) in addition to wood. The waste samples show lower reactivity peaks in the devolatilization stage, but higher reactivity peaks (located at lower temperatures) in the gasification and combustion stage, compared with those of reference biomass and construction woods. Mineral elemental analysis revealed that materials from various sources (gypsum, plastic, rust, paint, paint additives, and soils) were present in the samples. Soil recovered from the landfill contained higher Ca, Cu, Fe, K, Mn, Pb, and Zn levels than soil samples from elsewhere on the island. Results from this study can provide insight on variations in the physical and fuel properties of the CDW derived feedstocks, and support the design of conversion systems.